Konsep Pluralisme Hukum Khas Indonesia sebagai Strategi Menghadapi Era Modernisasi Hukum - Fradhana Putra Disantara (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2021)
The purpose of this legal research is to describe the concept of Indonesian legal pluralism or Indonesian legal pluralism in facing the era of legal modernization; as well as describing the Indonesian legal pluralism strategy in integrating customary courts into the national legal system. This legal research uses a statute approach and a conceptual approach. In this legal research, the primary and secondary legal materials used are inventoried in order to obtain proper legal review; and provides a conceptual analysis of the legal issues discussed. The results of the study stated that as a novelty concept; The concept of typical Indonesian legal pluralism provides equality for the enactment of state law, transnational law and customary law so that they can run together based on the 1945 Constitution of the Republic of Indonesia in the era of legal modernization. Then, the concept of typical Indonesian legal pluralism can be used as a strategy to integrate customary justice into the national legal system through aspects of legal development. Thus, this research is expected to be useful theoretically; namely as a scientific development of customary law, and practical benefits; namely as a reference for drafting regulations on customary villages by local governments. Therefore, researchers recommend that the Indigenous Peoples Bill be a priority in the 2021 National Legislation Program (Prolegnas).